Hydraulic response and nitrogen retention in bioretention mesocosms with regulated outlets part I--hydraulic response - Lucas, William C (Water environment research : a research publication of the Water Environment Federation, 2011)
In bioretention systems used for stormwater treatment, runoff interception improves with increased infiltration rates. However, nitrogen retention improves with increased retention time or decreasing infiltration rates. These contrasting responses were analyzed in 240-L experimental mesocosms using a variety of media treatments. The mesocosms were vegetated, except for one barren control. Dual-stage outlets were installed to extend retention time and equalize hydraulic responses. One unregulated treatment was free-draining. This part 1 paper presents the media properties and hydraulic responses. The highly aggregated media had saturated hydraulic conductivities ranging from 20.7 to 59.6 cm/h in August 2008 (austral winter), which increased to 42.8 to 110.6 cm/h in March 2009 (austral summer). The outlet regulated mesocosms provided retention over 8 times longer than the free-draining mesocosms, while still being able to capture large events. The outlets provide adaptive management for bioretention design to improve both runoff capture and nitrogen retention